Mechanism of spontaneous ignition of high-pressure hydrogen during its release through a tube with local contraction: A numerical study. (29th January 2022) - Jin, Kaiyan; Yang, Shengnan; Gong, Liang; Mo, Tianyu; Gao, Yunji; Zhang, Yuchun
Abstract: The tendency of spontaneous ignition of high-pressure hydrogen during its sudden release into a tube is one of the main threats to the safe application of hydrogen energy. A series of investigations have shown that the tube structure is a key factor affecting the spontaneous ignition of high-pressure hydrogen. In this paper, a numerical study is conducted to reveal the mechanism of spontaneous ignition of high-pressure hydrogen inside the tube with local contraction. Large Eddy Simulation, Renormalization Group, Eddy Dissipation Concept, 37-step detailed hydrogen combustion mechanism and 10-step like opening process of burst disk are employed. Three cases with burst pressures of 3.10, 4.90, and 8.45 MPa are simulated to compare against the pervious experimental study. The spontaneous conditions and positions agree well with the experimental results. The numerical results indicate that shock wave reflection takes place at the upstream vertical wall of contraction part. The interacted-shock-affected region is generated at the tube center because of the subsequent shock wave interaction. The forward reflected shock wave couples with normal shock wave and increases the pressure of leading shock wave. The sudden contraction of tube blocks the propagation of hydrogen jet and decreases the speed from supersonic flow to subsonic flow. More flammable mixture is generated inside the contraction part, as a results, the length of the flame is increased. Two mechanisms are proposed finally. Highlights: Mechanism of spontaneous ignition of high-pressure hydrogen in the tube with local contraction is numerically studied. Shock wave is reflected at the upstream vertical wall and interacts with each other at the tube center. A reflected-shock-affected region and an interacted-shock-affected region are formed. The results well reproduce the spontaneous ignition conditions and positions against previous experimental study.